PENERAPAN MEDIA PEMBELAJARAN DIGITAL ZEP QUIZ DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMAN 3 SUKOHARJO - Handayani, Rizka; Murtiningsih, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the application of the digital learning media Zep Quiz in increasing students' interest in learning, as well as to identify supporting and inhibiting factors from the perspective of teachers and students in the implementation of the Zep Quiz digital media. This study uses a descriptive qualitative approach with research subjects including the vice principal in the curriculum field, Pancasila Education teachers, and eleventh-grade students at SMAN 3 Sukoharjo. Data collection techniques were carried out through observation, interviews, documentation, and questionnaires, and then the data were analyzed using qualitative analysis techniques, which include data reduction, data presentation, and drawing conclusions. The research results show that the implementation of Zep Quiz is able to increase students' interest in learning, indicated by increased attention, high enthusiasm, active participation of students, and improving perseverance. Learning becomes more interactive and enjoyable through the use of quiz features and a ranking system. Supporting factors include the availability of facilities and infrastructure, the competence of teachers and students, school support in the form of policies and facilities, as well as students' characteristics that are adaptive to technology, while inhibiting factors include teachers' limited mastery of technology, less optimal time management, unstable internet network quality, and differences in the specifications of devices used by students. Thus, Zep Quiz is effective to be used as a digital learning medium to increase students' learning interest with adequate planning and facilities support.